1997
DOI: 10.1006/dbio.1997.8757
|View full text |Cite
|
Sign up to set email alerts
|

HNF-6 Is Expressed in Endoderm Derivatives and Nervous System of the Mouse Embryo and Participates to the Cross-Regulatory Network of Liver-Enriched Transcription Factors

Abstract: Hepatocyte nuclear factor-6 (HNF-6) is a liver-enriched transcription factor that contains a single cut domain and a novel type of homeodomain. Here we have studied the developmental expression pattern of HNF-6 in the mouse. In situ hybridization experiments showed that HNF-6 mRNA is detected in the liver at embryonic day (E) 9, at the onset of liver differentiation. HNF-6 mRNA disappeared transiently from the liver between E12.5 and E15. In transfection experiments HNF-6 stimulated the expression of HNF-4 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
125
1
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(131 citation statements)
references
References 42 publications
3
125
1
2
Order By: Relevance
“…This is somehow in contrast with the fact that in developing embryos, HNF-6 is expressed in a lineage-restricted manner [17]. However, several lineage-restricted factors, which include HNF-1α, HNF-1β and PDX-1 [29,34,35], are known to be expressed in undifferentiated ES cells and we show here that this is also the case for NGN-3.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…This is somehow in contrast with the fact that in developing embryos, HNF-6 is expressed in a lineage-restricted manner [17]. However, several lineage-restricted factors, which include HNF-1α, HNF-1β and PDX-1 [29,34,35], are known to be expressed in undifferentiated ES cells and we show here that this is also the case for NGN-3.…”
Section: Discussioncontrasting
confidence: 59%
“…During pancreas development, HNF-6 is expressed in the pre-pancreatic endoderm and in the pluripotent pancreatic epithelium that gives rise to the endocrine islets, to the exocrine acini and to the ducts. It is also weakly expressed in the acinar and ductal cells but not in the differentiated endocrine cells [17,18,19]. Gene knock-out studies in mice have shown that in the absence of HNF-6 the number of endocrine cells at birth is dramatically reduced [19].…”
mentioning
confidence: 99%
“…14,19 It has been proposed that GH induction of HNF-6 occurs via FoxA2 or HNF-4␣ transcriptional activation of HNF-6, or by GH effect on diminishing the repressive effect of C/EBP␣ on HNF-6 transcription. 20 HNF-6 in turn can transcriptionally regulate HNF-4␣, 21 suggesting the possibility that CYP7A1 transcriptional induction during GH treatment may be directly mediated via HNF-4␣ through GH-mediated increase in hepatic expression of HNF-6. Using wild-type CD1 mice, however, GH has a minimal effect on the expression levels of FoxA2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence suggests that maintenance of hepatocyte-specific expression of the HNF-6, HNF-4␣, FoxA2, and C/EBP␣ transcription factors involves cross-regulation by one or more unrelated liver-enriched transcription factors. 9,14,19,21 They have thus been proposed to participate in a complex network of autoregulatory loops to control hepatic gene expression. 20 The fact that we observed no change in hepatic expression of FoxA2, HNF-4␣, or C/EBP␣ following GH administration to wild-type CD1 mice suggests that GH-mediated stimulation of CYP7A1 is likely mediated through increased HNF-6 levels and not through the HNF-4␣ protein.…”
Section: Hnf-6 Foxa1mentioning
confidence: 99%
“…Two members of this class are present in mammalian liver, namely HNF-6 and Onecut-2 (OC-2) [14]. HNF-6 is expressed in the embryonic liver and pancreas [15,16] and it plays an important role in the development of these organs [17]. In the adult, HNF-6 is involved in the liver-specific control of several genes of glucose metabolism, e.g.…”
mentioning
confidence: 99%